The Effect of Hypnobreastfeeding Therapy on Self-Confidence Breastfeeding Mother at Mopuya Health Center - Ghea Oktareza; Anik Purwati (International Journal of Public Health, 2025)
A liquid with a comprehensive and diverse nutritional composition is breast milk (ASI). Hypnobreastfeeding is a relaxation method that helps moms feel more relaxed, peaceful, and at ease during the nursing process by giving them pleasant affirmations or suggestions. The Hypnobreastfeeding technique, commonly referred to as relaxation therapy, has been proposed as a means of overcoming these challenges and offering comfort to ensure a smooth nursing procedure. This study falls under the category of Quasy Experimental research, which is an experiment designed to identify a symptom or effect that appears prior to being administered After receiving hypnobreastfeeding treatment, an average score of 35.00 was attained. Since 0.000 is less than 0.05, the non-parametric Wilcoxon p-value is 0.000. It is anticipated that the findings of this study will serve as foundational information for future research. Researchers advise studying how mothers see the value of exclusively nursing infants.Effective hypnobreastfeeding practices are necessary for management aimed at boosting the influence of self-confidence. When it comes to boosting breastfeeding moms' self-confidence, this move is highly successful. Smooth breast milk is one of the factors contributing to the limited coverage of exclusive breastfeeding. The cause of not smooth breast milk is a decrease in Lack of stimulation of the hormones prolactin and oxytocin, which are crucial for the smooth production of breast milk, is the reason of breast milk production in the first few days after birth. Babies that get inadequate nursing will have bloated, red, and malnourished breasts, making them more vulnerable to a variety of illnesses. Hypnobreastfeeding is one method to boost the production of breast milk. The advantages of exclusive breastfeeding are numerous: it can give kids the best nourishment possible; breast milk is simpler to digest than formula milk; it is high in antibodies to boost immunity; it strengthens the emotional tie between mother and child; and it can boost children's IQ (Wijaya, 2019). The purpose of this case study is to describe the application of hypnobreastfeeding relaxation techniques to breastfeeding mothers. The method used in this case study is a descriptive method with an evaluation of hypnobreastfeeding actions. The results after hypnobreastfeeding therapy with a frequency of 3x a day with a duration of 10-30 minutes for 3 days showed an increase in self-confidence in 29 respondents. In conclusion, hypnobreastfeeding is effective in helping to increase the self-confidence of breastfeeding mothers. Hypnobreastfeeding has been proven effective in increasing self-confidence experienced during pregnancy and after childbirth. The results of data analysis using Man Whitney showed a significant difference in anxiety between the group given the intervention and the group that was not given the hypnobreastfeeding intervention. The characteristics of the study subjects were evenly distributed across groups so that the parity factor did not affect the results of the study as a confounding factor.